Mortality and associated risk factors in perioperative acute kidney injury treated with continuous renal replacement therapy - Uusalo Panu; Hellman Tapio; Järvisalo Mikko J. (BioMed Central, 2022)
Background: Perioperative acute kidney injury (AKI) is associated with multiple postoperative complications leading to prolonged hospital stay and higher costs. AKI requiring continuous renal replacement therapy (CRRT) after surgery has an incidence of 2-6% and mortality approximates 40-60%. Previous studies examining mortality in perioperative AKI patients managed with CRRT have concentrated on cardiac surgery patients and there are very limited data on broad surgical patient populations requiring CRRT. We examined long-term mortality and factors associated with poor outcome in a broad surgical population requiring CRRT for perioperative AKI during a 10-year period.Methods: Surgical patients admitted to the intensive care unit (ICU) of academic tertiary hospital requiring CRRT between years 2010-2019 were included. CRRT was performed using regional citrate-calcium-anticoagulation. Extracted data included patient demographics, comorbidities, and clinical parameters at ICU admission and at the initiation of CRRT. Creatinine and estimated glomerular filtration rate (eGFR) were measured at 1 year after ICU admission.Results: A total of 157 patients were included in the study. ICU mortality was 42.7%, 90-day mortality 58.0% and 1year mortality 62.4%. Blood lactate at ICU admission and CRRT initiation were independently associated with mortality in the multivariate models. Patients with lactate > 4 mmol/l had higher mortality than patients with normal lactate (77% vs. 21%) (p < 0.001). Creatinine (p = 0.004) and eGFR (p < 0.001) remained significantly altered at 1 year of follow-up compared to baseline.Conclusions: Patients undergoing surgery and requiring perioperative CRRT in the ICU have a high risk of mortality. Mortality appears to be independently associated with lactate levels.